The usefulness of combined brain perfusion single‐photon emission computed tomography, Dopamine‐transporter single‐photon emission computed tomography, and 123I‐metaiodobenzylguanidine myocardial scintigraphy for the diagnosis of dementia with Lewy bodies. Issue 4 (28th January 2017) - Kobayashi, Seiju; Makino, Kanae; Hatakeyama, Shigeki; Ishii, Takao; Tateno, Masaru; Iwamoto, Tomo; Tsujino, Hanako; Kawasaki, Kazuhito; Mikuni, Kouhei; Ukai, Wataru; Murayama, Tomonori; Hashimoto, Eri; et al.
Abstract : Background: Current diagnostic criteria recommend neuroimaging as a diagnostic support tool for the clinical diagnosis of dementia with Lewy bodies (DLB). Because DLB causes characteristic impairments and disabilities, such as neuroleptic hypersensitivity, which may significantly increase morbidity and mortality, its prompt and correct diagnosis is very important. The aim of this study was to evaluate the extent to which diagnostic accuracy can be increased by using different combinations of brain perfusion single‐photon emission computed tomography (bp‐SPECT), 123 I‐metaiodobenzylguanidine myocardial scintigraphy (MIBG scintigraphy), and DAT‐SPECT. Taking finances and patient burden into consideration, we compared the tests to determine priority. Methods: Thirty‐four patients with probable DLB (75.0 ± 8.3 years old; 14 men, 20 women) underwent bp‐SPECT, MIBG scintigraphy, and DAT‐SPECT. Results: Our comparison of three functional imaging techniques indicated that MIBG scintigraphy (79%) and Dopamine‐transporter (DAT) SPECT (79%) had better sensitivity for characteristic abnormalities in DLB than bp‐SPECT (53%). The combination of the three modalities could increase sensitivity for diagnosis of DLB to 100%. Additionally, the ratio of patients with rapid eye movement sleep behaviour disorder was significantly higher in the positive finding group on MIBG scintigraphy than in the negative finding group. Conclusions: In terms of stand‐alone diagnostic means, priority should be placed on MIBG scintigraphy or DAT‐SPECT for the diagnosis of DLB. However, our results suggest that the combination of bp‐SPECT, MIBG scintigraphy, and DAT‐SPECT increased the accuracy of the clinical diagnosis of DLB.